2014
DOI: 10.1186/1472-6939-15-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceived purpose of clinical informed consent: Mill’s individual autonomy model is preferred

Abstract: BackgroundAlthough informed consent is an integral part of clinical practice, its current doctrine remains mostly a matter of law and mainstream ethics rather than empirical research. There are scarce empirical data on patients’ perceived purpose of informed consent, which may include administrative routine/courtesy gesture, simple honest permission, informed permission, patient-clinician shared decision-making, and enabling patient’s self decision-making. Different purposes require different processes.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
2
31
0
1
Order By: Relevance
“…These results were different from Hammami et al where nearly all participants (95.7%) were aware that their next of kin could sign on their behalf. 4 The results of this study revealed that there is a significant weak positive correlation between patient's knowledge and perception of patients towards informed consent for surgical procedures (r = 0.487), (-1≤ r ≤1, p=0.00). This means that as the patient' knowledge increases the perception also increases towards informed consent for surgical procedures.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These results were different from Hammami et al where nearly all participants (95.7%) were aware that their next of kin could sign on their behalf. 4 The results of this study revealed that there is a significant weak positive correlation between patient's knowledge and perception of patients towards informed consent for surgical procedures (r = 0.487), (-1≤ r ≤1, p=0.00). This means that as the patient' knowledge increases the perception also increases towards informed consent for surgical procedures.…”
Section: Discussionmentioning
confidence: 71%
“…3 Informed consent is built on patient competence to understand information and making a deliberate decision to undergo a specific surgical procedure and is valid until the patient' disease has not been changed or no new findings that may change the planned procedure are revealed. 4 Patient's self-reflection should be empowered as it enables them to take treatment decisions themselves. Nevertheless, poor patient's perception to informed consent compromises their autonomy and self-determination, therefore they feel powerless and unaccountable for their treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Personal choices are only accepted if they are the "right" ones. [6] However, Hammami et al [7] concluded in their survey study with 488 Saudi patients (both male and female) that their results showed a strong sense of individual autonomy orientation, a strong sense of self-efficacy, and reduced trust in the healthcare system. However, Marrone, [8] argued that Saudi women usually will defer to their husband's or father's decision making.…”
Section: Self-determination and Autonomymentioning
confidence: 99%
“…Surgical informed consent is the process whereby patients are informed of all the necessary information about health care and subsequent treatment plans, risk, and alternatives. An informed consent is built by competent patient to make decision about his/her surgical procedure with enough information which is clear and understandable and valid unless the patient's disease has not been changed, and or no new findings that may change the planned procedure are revealed (1). Whatever it is, the patient has still full right to refuse the treatment, called informed refusal, but the reality is not true in clinical practice (2,3).…”
Section: Introductionmentioning
confidence: 99%